Heritage and patrimony of the peasantry framework to address rural development and its application in Colombia - Fabio Alberto Pachón Ariza; Wolfgang Bokelmann; César Adrián Ramírez Miranda (Acta Agronómica)
The theoretical framework “heritage and patrimony of the peasantry” and its suggested operationalization potentially offers an improvement over previous approaches to analyse rural development. The first application of the concept was carried out in Colombia, quantifying rural development indicators in six rural territories. The most critical indicators to define rural development in this context were identified as follows: biodiversity, recycling and communal values. Based on these findings, human patrimony has the lowest level of all the heritages of the Colombian peasantry. Public policies to overcome these matters in the post-conflict era, should be the priority of rural development strategies.